Buster - Huett, Caleb Zane (New York : Scholastic Inc., 2022)
"Buster's a therapy dog who needs to take matters into his own paws to help a boy understand his own anxiety--even if it means breaking a few rules."--
Includes an excerpt from Buster undercover.
Keywords: Service dogs -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Anxiety -- Juvenile fiction; People with disabilities -- Juvenile fiction; Friendship -- Juvenile fiction; Animal fiction